Genotypic richness of Phragmites australis negatively impacts ecosystem multifunctionality in the coastal wetland of Yellow River Delta, China - Liwen Zhang; Lianjun Zhao; Siqun Lan; Lin Chen; Guangxuan Han (Global Ecology and Conservation)
The study of the relationship between genetic diversity and ecosystem functions (EFs) primarily focuses on the relationship between species diversity and EFs, with less emphasis on investigating the connection between genetic diversity and EFs, particularly in relation to ecosystem multifunctionality. We conducted an outdoor common garden experiment to manipulate the genotypic richness of Phragmites australis and investigate its relationship with ecosystem multifunctionality in the coastal wetland of the Yellow River Delta. Our findings revealed that the impact of genotypic richness of P. australis on EFs varied in the coastal wetland of the Yellow River Delta, particularly with regards to soil bacterial richness, where P. australis genetic richness has been found to exert a significantly negative effect. The analysis further demonstrated that as genotypic richness increased, there was a corresponding decreasing trend in the average multifunctionality index. This could be attributed to competitions among genotypes leading to a reduction in ecosystem multifunctionality. Furthermore, when considering different thresholds (the proportion of EF reaching their maximum value) for EF (20 %, 40 %, and 60 %), higher genotypic richness led to an increased number of EFs attaining the maximum value. However, at the higher level (80 %) threshold, higher genotypic richness reduced the number of EFs reaching the maximum value. Our study demonstrated that an increase in plant genotypic richness may reduce ecosystem multifunctionality. It suggests that the introduction of new genotypes into an ecosystem may potentially reduce its multifunctionality, thus caution should be exercised when introducing new genotypes.